Dynamic Search Mechanism with Threat Prediction in a GNSS Receiver - Fang Liu; Meng Liu (Journal of Electrical and Computer Engineering)
With the development of GNSS and the application of multimode signals, efficient GNSS receiver research has become very important. However, threat signals in the received signal are inevitable, which will represent important threats to navigation applications and will lead to leakage and fault detection for the receiver. Therefore, the searches with threat prediction in GNSS signals have been regarded as the important problem for GNSS receivers. In view of the limitations and nonadaptability of the current search technologies as well as on the basis of the proportionality peak judgment mechanism, a dynamic search mechanism with threat prediction (DSM-TP) is proposed in this paper, in which we define a series of preset coefficients and a threat index to optimize the decision mechanism. The simulation results demonstrate that the DSM-TP method can predict the threat situation and can adapt to lower SNR environments compared to the traditional method. In addition, the DSM-TP method can avoid the impact of threats, and the detection capability of the new method is better than the detection capability of the traditional method.